Head position control strategies in progressive Supranuclear Palsy versus Idiopathic Parkinson’s Disease during dynamic-on-static platform tilt - Stefan Kammermeier; Kathrin Maierbeck; Kathrin Maierbeck; Lucia Dietrich; Lucia Dietrich; Annika Eissner; Stefan Lorenzl; Stefan Lorenzl; Arun Singh; Arun Singh; Kai Bötzel; Christoph Maurer (Frontiers in Neurology)
ObjectivesWe investigated differences in head stabilization among Progressive Supranuclear Palsy (PSP), advanced Idiopathic Parkinson’s Disease (IPD) and healthy controls during passive anteroposterior platform tilting to determine factors for disease-specific falling.MethodsSeventeen PSP, eleven IPD and eighteen control subjects were exposed to pseudorandom multi-frequency antero-posterior platform tilts, while recording 3D motion of body segments with a Zebris ultrasound positioning system. Fourier transforms were computed from the time series datasets to assess transfer functions between stimuli (platform tilts) and responses (angles of the head, trunk and hip in space).ResultsOverall head excursions in space among PSP was several times increased in relation to IPD and controls. The stimulus driven contribution to the head movement, i.e., the GAIN of the transfer function between platform stimulus and head movement, was double the amount of the values derived from IPD and 5-fold relative to controls. GAIN of the transfer function was the highest among the middle tilt frequencies 0.15–0.4 Hz, and was independent from the eyes open vs. closed condition.ConclusionPSP patients’ head excursions with respect to the shoulder girdle and trunk were exceptionally increased, compared to IPD and controls. The source for the larger excursions, however, was not related to an unspecific lack of head stabilization, but was instead determined by a central strategy. Consistent with pathoanatomical degeneration of mesencephalic supracollicular pathways processing visual flow or vestibular pathways, PSP resorted to egocentric proprioceptive-dominated stabilization to the surface, rather than allocentric stabilization in space like IPD. Passive neck rigidity in PSP did not contribute significantly.SignificanceThe axial muscle rigidity emphasized in PSP versus IPD did not contribute to body instability in the sensory context of unstable surfaces. Instead, deficits in processing of visual and vestibular information played a larger role in PSP falling than previously known.